Philosopher gone wild: Rolston bio-photo-media 2020 - Rolston, Holmes, 1932-2025, speaker and filmmaker (Colorado State University. Libraries, 2020)
Holmes Rolston's biography: Shenandoah Valley childhood. Education. Years in Southwest Virginia. Grand Canyon River run. Colorado State University, classroom. Interview, University of Georgia. Family and outdoors. Rolston-Rollin debate, 1989. Wild Rockies, including wolves. Travels, Africa, Asia including Nepal, and Antarctica. Science and Religion. Oakland University, Michigan, Gifford Lectures, Edinburgh, 1997-1998. Wilderness. Templeton Prize in Buckingham Palace, 2003. In the woods. Endowed Rolston Chairs, Davidson College, CSU. The Pasqueflower, 2008.
Photo-media biography compiled in 2008. Includes personal history with photographs; personal travels with photographs; and portions of lectures, interviews and presentations. Revised in 2020.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: biography; Rolston, Holmes, 1932-2025